Quasi Two-Dimensional Si-O Superlattices: Atomically Controlled Growth and Electrical Properties. (1st January 2016) - Jayachandran, Suseendran; Simoen, Eddy; Martens, Koen; Meersschaut, Johan; Bender, Hugo; Caymax, Matty; Vandervorst, Wilfried; Heyns, Marc; Delabie, Annelies
Abstract : We perform a systematic study on the growth of epitaxial Silicon–Oxygen superlattices (SLs) and investigate the impact of structural properties on the electrical performance. Si layers and O atomic layers (ALs) are deposited using SiH4 and O3 reactions respectively. Although the deposition of O ALs and epitaxial Si thereon, i.e. 1 st period of Si–O SL is well documented, the controlled deposition in maintaining the overall crystalline quality of SL is still a challenge. This is due to inability to limit the O layer to sub-AL content (1AL = 6.7 × 10 14 at/cm 2 ) at higher periods (≥2). The Si surface prior to O AL deposition is chemically modified with H-passivation and sub-AL O-content is achieved. This ensures minimum structural distortions, enabling epitaxial ordering of Si and hence the epitaxial Si–O SL up to 5-periods. No SiOx clusters are detected and O layers are stable at Si deposition temperature. Electrically, donor defects increase with Si–O periods and partially reduced with forming gas anneal. The presence of defects and increased roughness during the growth, degrade the mobility due to coulomb and surface scattering respectively. It can be circumvented by optimizing SL parameters and other process integration parameters subjected for future research.